A simple method for the prevention of endometrial autolysis in hysterectomy specimens. Issue 3 (27th February 2004) - Houghton, J P; Roddy, S; Carroll, S; McCluggage, W G
Abstract : Aims: Uteri are among the most common surgical pathology specimens. Assessment of the endometrium is often difficult because of pronounced tissue autolysis. This study describes a simple method to prevent endometrial autolysis and aid in interpretation of the endometrium. Methods: Sixty uteri were injected with formalin using a needle and syringe directed alongside a probe, which was inserted through the external cervical os into the endometrial cavity. Injection was performed on the same day as removal of the uterus. As controls, 60 uteri that were not injected with formalin were examined. The degree of endometrial autolysis was assessed on a four point scale (0–3), with a score of 0 representing no or minimal autolysis and a score of 3 representing extensive autolysis, such that histological interpretation of the endometrium was impossible. Results: In the injected group, the number of cases with scores of 0, 1, 2, and 3 was 42, 13, four, and one, respectively. The corresponding values for the control group were 17, 23, eight, and 12, respectively. This was highly significant (p < 0.001) Conclusions: There was significantly less endometrial autolysis in uteri injected with formalin. The use of this simple procedure should be encouraged in hysterectomy specimens.